A efetividade do Fundef e Fundeb como instrumento de financiamento do direito à educação básica e as perspectivas do novo Fundeb - Galdino, Marli (2020)
The history of education in Brazil as a secured right was marked by dominant traces from catholic, agrarian and slavery culture, reflecting a disorganized selective elitist educational system. Such facts resulted in a high level of illiteracy that only started to decrease after the enactment of the 1988’s Federal Constitution, since the past educational reforms related to equity, financing, access and teaching quality. From 1990, with the purpose to mitigate the regional educational inequalities still existent, handle scholar explosion and eliminate any traces from the past period gaps, were created other educational funding mechanisms, firstly, The Middle School and Teaching Appreciation Maintenance and Development Fund - Fundef, extinct in 2006, and after its successor. The Elementary School and Teaching Professionals Appreciation Maintenance and Development Fund - Fundeb, valid until December 2020. The research presented in this dissertation has as a main objective to examine the education funding mechanisms, to verify in which extent this special funds resources contributed to the effectiveness of education’s maintenance and development. Still, the constitutional amendment presented to the Congress and Senate that have as an objective the creation of a new permanent and qualitative Fundeb were analyzed, preventing the increase of Union’s resources complementation. The research was based on the analyses of the historical process of the right to education until its consecration fundamental social right and the education funding structuring policy in Brazil